FEATURES OF INTERPRETATION OF THE RESULTS OF HOLTER MONITORING IN THE AGE CATEGORY OF THE POPULATION - K.E. Gubskaya; Y.T Tolegenov; D.A Urazalina (Interdisciplinary Approaches to Medicine)
The research topic is designated as the features of interpretation of the results of Holter monitoring of the age category of patients and attention to these aspects for decision-making. The aim of the study is to identify image indicators in the parameters of Holter monitoring in patients in the space with a general age population. The article considers the conditions for updating Holter monitoring in screening for the risk of developing cardiovascular diseases for the age category of patients both in early prediction and in the current state of the cardiovascular system. An information search was conducted in two specialized information resources: PubMed and TripDataBase. The search was carried out using the PICOS methodology with a comparative assessment using the PRISMA methodology. Six studies were provided for analysis, including 4 RCTs and 2 cohort studies. The degree of separation of the basic indicators of the Holter Diptych in low- and high-frequency modes is noted. Age features are noted in assessing heart rate variability. Differences in age-related changes in Holter monitoring indicators in circadian rhythm are also noted. All this provides information for practicing specialists on the appointment of Holter monitoring for age-related patients.